Human and artificial intelligence/s: to rethink the human being from theology - Oio, Pablo Damián (Razón y fe, 2024)
Intelligence distinguishes human beings and is an expression of the dignity that God gives to each person. In psychology, various theories have been proposed about intelligence. The progress of technologies and artificial intelligence (AI) opens new questions, not only for the sciences but also for theology. In times of transhumanism, the development of artificial intelligence and its consequences give the opportunity to rethink the human being from theological anthropology, with a fruitful dialogue between faith and science.